If it's not what You are looking for type in the equation solver your own equation and let us solve it.
y=-(1/3y-13/3)+2
We simplify the equation to the form, which is simple to understand
y=-(1/3y-13/3)+2
Remove unnecessary parentheses
y=-3y+4.3333333333333+2
We move all terms containing y to the left and all other terms to the right.
+1y+3y=+4.3333333333333+2
We simplify left and right side of the equation.
+4y=+6.3333333333333
We divide both sides of the equation by 4 to get y.
y=1.5833333333333
| x^3-36x+72=0 | | 14a-21b+35= | | x=1/3(-x+2)-13/3 | | s-2w=0 | | 20x+50y+5z=500 | | 16a+8b+c=100 | | 8a^3-6a^2= | | 6y^2-36y+324=0 | | 14m^2n+7mn= | | (7n-1)(n+2)=0 | | 2y-12(2y)+32=0 | | 2s-3w=1 | | 2x^9-14x^7=0 | | (p+7)(p+2)=0 | | 3x-12=-x+4 | | 6p^2=-31p | | 2ln-9x=0 | | 8+ln-5n=7 | | 2+4x=55-41 | | 3(x+2)-2(x+1)= | | 50x^2+50x+50000000= | | 9000=92*1.8t | | w^2-12+3=0 | | 9(x+27)=4x-3 | | 8+5=31 | | 0=-25t^2+150t+200 | | 0=t^2-6t-8 | | 50x+20y+5z=500 | | x=17.5+-1y | | 35=2x+2y | | 3(5x+9)=4(7x+5) | | lnx+ln*2=3 |